Polycaprolactone based pharmaceutical nanoemulsion loaded with acriflavine: optimization and in vivo burn wound healing activity. (31st December 2022) - Nawaz, Touseef; Iqbal, Muhammad; Khan, Barkat Ali; Ahmed, Naveed; Nawaz, Asif; Rasul, Akhtar; Rizg, Waleed Y.; Jali, Abdulmajeed M.; Ahmed, Rayan A.; Safhi, Awaji Y.
Abstract: Cutaneous burn wounds are a common and troublesome critical issue of public health. Over the last decade, many researchers have investigated the development of novel therapeutic modalities which are capable of fully regeneration and reinstatement of structure and function of the skin with no or limited scar formation. Novel pharmaceutical carriers are offering a potential platform to deliver the drug effectively and to overcome the limitation associated with conventional wound dressings. The aim of this study was to investigate a pharmaceutical acriflavine-loaded polycaprolactone nanoemulsion (ACR-PCL-NE) for burn wound healing. Nanoemulsion was prepared by using the double emulsion solvent evaporation technique and it was subjected to thermodynamic stability testing, droplet size, polydispersity, zeta potential, pH, and surface morphology analysis. The in vivo study was performed to evaluate the efficacy of nanoemulsion using Sprague-Dawley rats as an animal model. The results of this study revealed that the optimized nanoemulsion was stable and had desirable physicochemical properties. The pH was about 4.02 at 25 °C and the particle size was found to be in the range of 302 ± 4.62 nm while the zeta potential was −7.8 ± 1.22 mV and the polydispersity index of 0.221 ± 0.017. The wound regeneration process was evaluated in vivo by different techniques, the formulation group (FG) showed high wound healing potential as compared to the standard group (SD) and control group (CG). These findings reveal that this nanoemulsion formulation can be used effectively for wound healing.